If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 = x(13 + x) 48 = (13 * x + x * x) 48 = (13x + x2) Solving 48 = 13x + x2 Solving for variable 'x'. Reorder the terms: 48 + -13x + -1x2 = 13x + -13x + x2 + -1x2 Combine like terms: 13x + -13x = 0 48 + -13x + -1x2 = 0 + x2 + -1x2 48 + -13x + -1x2 = x2 + -1x2 Combine like terms: x2 + -1x2 = 0 48 + -13x + -1x2 = 0 Factor a trinomial. (3 + -1x)(16 + x) = 0Subproblem 1
Set the factor '(3 + -1x)' equal to zero and attempt to solve: Simplifying 3 + -1x = 0 Solving 3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1x = 0 + -3 -1x = 0 + -3 Combine like terms: 0 + -3 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3Subproblem 2
Set the factor '(16 + x)' equal to zero and attempt to solve: Simplifying 16 + x = 0 Solving 16 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + x = 0 + -16 Combine like terms: 16 + -16 = 0 0 + x = 0 + -16 x = 0 + -16 Combine like terms: 0 + -16 = -16 x = -16 Simplifying x = -16Solution
x = {3, -16}
| 25-8(n+2)=1 | | 13(x-9)-2=7x-5 | | -3x+16=28 | | 10x^2-16=0 | | 17y-8y=63 | | 1+y=-y-13 | | -6(x-4)+2=68 | | y=5x^2+3x-1 | | 1+y=-y-31 | | x=5y^2+3y-1 | | 2z+5=5z-8 | | (7x-4)8.4= | | d^2+9d+14=0 | | 11-2y=3-y | | g(-5)=(-56)-6 | | 40=x(14-x) | | 21x-30x-7=20 | | 53=10(u-93)+13 | | 3(2c+d)-4(c-d)+d^2= | | 3h^2-2=10 | | 13p+15p+15=43 | | y=8x-2/x^3 | | 16=8x-x^2 | | 3sinx=1-3cosx | | -20/t=-4 | | Y+8.71=3.8 | | 0.3x-0.5y=6.7 | | 2log^4=16 | | 87n+-11n+-85n=-27 | | 4/8=x/12 | | 0.25x+0.10(30-x)=5.58 | | Y-1/2=1/4 |